Diversity, abundance, and ecological roles of insect pollinators in red guava flowers (Psidium guajava) in East Java, Indonesia - BUDI PURWANTININGSIH; AMIN SETYO LEKSONO; BAGYO YANUWIYADI; ZULFAIDAH PENATA GAMA; SAIFUL ARIF ABDULLAH (Society for Indonesian Biodiversity, 2025)
Abstract. Purwantiningsih B, Leksono AS, Yanuwiyadi B, Gama ZP, Abdullah SA. 2025. Diversity, abundance, and ecological roles of insect pollinators in red guava flowers (Psidium guajava) in East Java, Indonesia. Biodiversitas 26: 1211-1219. Red guava (Psidium guajava) is a high-value crop with relatively easy cultivation requirements. However, the decline in pollinating insects is a global issue that has led to reduced guava productivity and harvest yields. This study aimed to analyze the abundance, richness, diversity, evenness, and dominance of insects visiting red guava flowers, as well as to visually examine their visitation patterns across five locations in East Java, Indonesia: Pademonegoro, Tlekung, Oro-Oro Ombo, Junrejo, and Mulyoagung, and assess the ecological roles. A total of 3432 individual insects from 17 families and five orders were identified, with pollinators dominating in all locations. Junrejo exhibited the highest abundance (29.11%) but low diversity (0.78), whereas Pademonegoro had the highest diversity (1.80) with moderate abundance. Statistical analysis revealed no significant differences in insect composition between locations (p>0.05), although PCA analysis indicated variations in insect characteristics at certain sites. Insect activity was influenced by flowering periods, temperature, and light intensity, with peak activity varying across locations. These findings underscore the critical role of pollinators, particularly the Apidae family, in red guava pollination, highlighting their significant contribution. The study also highlights the diverse adaptations of insect communities to their local environments, providing insights into sustainable agroecosystem management through pollinator conservation.